GOVERNMENT SPENDING AND ECONOMIC DISASTER THEORY IN POST ASIAN FINANCIAL CRISIS IN 1997 & GLOBAL FINANCIAL CRISIS 2008 IMPACT IN MALAYSIA - MOHD AZLAN ABDUL MAJID; Faridah Pardi; Muhammad Khodri Kholib Jati; Suzana Hasan (Journal of Academia, 2022)
This research intent to investigates the Economic Disaster Theory of the past of recent shock to Malaysia in of Asian Financial Crisis in 1997 and compare to Global Financial Crisis in 2008 and testing economic disaster theorem. From the past-history of economic argument from Classism of Adam Smith to Modern Keynesian model, the importance of fiscal policy is too vital in controlling and mitigate especially economic downturn. The case is arisen with focus in investigate Economic Disaster theory and compare with two shocks impact in Malaysian cases. We take the data from 1974 to 2020, and use simple time series, Cholesky decomposition and time series method. As in Economic Disaster Theorem itself, the theory state that in shock time, consumption and government will have positive relationship while investment and net export will persist negative relationship to income. This because government is only institution that can react in ad hoc time-period and if Malaysian cases shock economics disaster theorem hold, this will reflect the and rejoice of our predecessor argument of Keynesian tenet and support the J-Curve relationship. The output shows that long run ARDL show partial supported the economic disaster theorem while Cholesky impulse shows supported economic disaster theorem. Government Spending is powerful tools, and this study validates the importance of New Keynesian tenet.